Bahasa Inggris - Aniah, Anggun; Sari, Maylia Pramono; Anita, Nur (Politeknik Keuangan Negara STAN, 2025)
This study investigates the impact of media exposure, firm size, and board size on carbon emission disclosure, with environmental performance as a moderating variable. The population comprised 62 mining companies listed on the Indonesia Stock Exchange, observed over five years from 2018 to 2022. This study uses purposive sampling with a sample of 28 companies, and 74 units of analysis were selected. The data were analyzed using SPSS 26 software, employing the Moderated Regression Analysis (MRA) technique. The results indicate that firm size and board size positively influence carbon emission disclosure, while media exposure does not have a significant effect. Environmental performance strengthens the positive relationship between firm size and carbon emission disclosure but does not moderate the impact of media exposure and board size on carbon emission disclosure.